Uji Aplikasi Kapur dan Fosfogipsum Terhadap Sifat Fisika, Kimia Typic Kanhapludult dan Parameter Agronomis Tebudi Lampung Tengah - Notohadisuwarno Notohadisuwarno (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2017)
The aim of the resarch to obtainedphosphogypsum and liming rate affectUltisol properties and sugarcane performance in Gunung Madu Plantation, Lampung Tengah. Ultisol problems in aidity, Al-toxicity, low cation exchange capacity (CEC), and base saturation (BS) caused low yield of sugarcane. The experiment was arranged by completely randomized block design, with 12 treatment and 3 replicates of each treatment.Chemical nutrient status in soil dan nutrient leaf content and plant was observed each 2 month after phosphogypsum and lime application. Physical properties was observed 4 month after phosphogypsum and lime application. Sugarcane growth parameters were observed in each month after planting, biomass sample harvested in end of vegetative phase. The result of this study was showed that phosphogypsum and lime application increased soil pH,sulfur leaf content, aggregate stability, permeability, sugarcane performance and decreased Al toxicity.Keyword : soil amendment, calcium source, red yellow podzol, agronomic properties, sulfur.